DETERMINAN TINGKAT PENGUNGKAPAN LKPD DI INDONESIA: INTERNAL CONTROL SYSTEM SEBAGAI VARIABEL MODERASI - Novita Putri Utami (2023)
This research was conducted to examine what factors can affect the level of disclosure of local government financial statements, this study uses the internal control system as a moderating variable. The independent variables used in this study are financial condition, capital expenditure, wealth region, and government size, as well as the level of disclosure of local government financial reports (LKPD) as the dependent variable. This study uses the 2021 district/city LKPD population in Indonesia which has been audited by the BPK. The number of research samples used was 479 LKPD with purposive sampling as the sampling technique. The data analysis technique used in this study is Structural Equation Model-Partial Least Square (SEM-PLS) Version 3. Based on the test results, it was found that financial conditions, capital expenditure, region wealth, and government size have a significant effect on the level of LKPD disclosure. The internal control system as a moderating variable cannot moderate the effect of financial conditions, capital expenditure, region wealth and government size on the level of LKPD disclosure.